ENGLISH FOR SECRETARY: Echancing Professional Communication in the Office Environment - Lestari Putri, Gunaningtyas Ayu (Nsc Press, 2025)
The secretary profession requires professional communication skills, including English proficiency as a global communication tool. This article discusses the importance of mastering English for Secretary in the context of a modern work environment, as well as strategies for teaching English relevant to the needs of secretaries. This study uses a qualitative approach with literature studies and observations of the language needs of secretaries. The findings show that English language competencies, including business correspondence, verbal communication, and interpersonal skills, are key factors in supporting a secretary's professionalism